THE IMPACT OF TEAM PAIR SOLO TECHNIQUE AND ROUND ROBIN TECHNIQUE ON STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This journal is based on a study which attempts to improve the students’ writing ability of the seventh grade students of SMP Negeri 1 Parakan to write descriptive text using Team Pair Solo technique and Round Robin technique. The study aimed to examine the effectiveness of Team Pair Solo technique and Round Robin technique to improve students’ ability in writing descriptive text. Test and scoring system were used as the instruments to collect the data needed. Pre-test and post-test were given to both experimental group and comparison group. In the treatments, the students of the experimental group were taught using team pair solo technique. On the other hand, the students of comparison group were taught using round robin technique. Posttest was given after the treatments. The t-test result showed that tvalue was 2.64 and ttable for σ = 5% was 2.01. It can be clearly seen that tvalue is higher than the critical value (2.64>2.01). It means that the hypothesis of H1 is accepted and H0 is refused. Based on the proven hypotheses, the writer can conclude and assume that Team Pair Solo technique and Round Robin technique are proven effective to be implemented in teaching written descriptive text for seventh grade students at secondary school.